Effects of the teaching of sentences on recombinative reading with comprehension: CRMTS procedure (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
The objective of this study was to investigate the effects of the teaching of sentences using the constructed response matching to sample procedure (CRMTS) on recombinative reading with comprehension. Participants were five children from the Basic Education. First relations AB and AE were taught and the relations BE/EB tested. After, there was the teaching of CB and DB relations and the test of C’B relation. Finally, the relations FB was taught and the relations FB’, DC and CD were tested. The letter A represents the class of the spoken word, B printed word, C printed sentence, D spoken sentences, E figure, F colors, B’ new printed words and C’ new printed sentences. All participants learned the taught relations. Three participants had 100% of correct responses in the BE, EB and C’B tests and all of them had 100% of correct responses in the FB’, DC and CD tests. The results suggest that the procedure was effective in generate generalized recombinative reading and reading with comprehension.
Keywords: symbolic behavior; teaching of sentences; recombinative reading; CRMTS